Can Government Intervention Make Firms More Investment Ready? A Randomized Experiment in the Western Balkans - Cusolito, Ana Paula; Dautovic, Ernest; McKenzie, David (The Review of Economics and Statistics, 2021)
Abstract Innovative firms with good ideas may still struggle to fine-tune them to the stage where they can attract outside funding. We conduct a five-country randomized experiment that tests the impact of an investment readiness program. Firms then pitched their ideas to independent judges. The program resulted in a 0.3 standard deviation increase in the investment readiness score. Two years later, the average impacts on firm investment outcomes are positive but small in magnitude and not statistically significant. Larger and statistically significant impacts on receiving outside funding occur for smaller firms and for firms with lower likelihoods of otherwise being funded.